2014
DOI: 10.1159/000365864
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Aspects of Decompression Craniectomy in Malignant Stroke: Review

Abstract: Background: Space-occupying malignant stroke of the middle cerebral artery (MCA) is associated with a high mortality rate of up to 80% under conservative treatment. Although there is convincing evidence that decompression craniectomy can significantly reduce mortality rate and improve neurological outcome in young patients (<60 years), many surgeons are still hesitant to recommend hemicraniectomy for stroke patients. Summary: This review addresses some major issues that appear to be an obstacle to decompressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 84 publications
(180 reference statements)
1
42
0
7
Order By: Relevance
“…Moreover, Zweckberger et al [24] summarize that complications after DHC in MMI have never been systematically assessed. We found that patients with MMI who have undergone DHC are prone to a high rate of complications in the acute as well as in the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zweckberger et al [24] summarize that complications after DHC in MMI have never been systematically assessed. We found that patients with MMI who have undergone DHC are prone to a high rate of complications in the acute as well as in the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of stroke-induced disabilities can reach as high as 80% (15). Stroke-induced disabilities can have a serious effect on the daily life of the patient, bring great suffering and place a heavy burden on the family and society (16).…”
Section: Discussionmentioning
confidence: 99%
“…The most optimal time for subsequent cranioplasty is 1.5-6 months after DC [17,18,89]. In addition, the number of complications reaches 26%: epileptic attacks 15.6%, superficial wound infections 3.1%, hydrocephaly 3.1%, transient neurological impairments 3.1%, and osteomyelitis 2.1% [90].…”
Section: Malignant Ischemic Stroke Therapymentioning
confidence: 99%
“…The main DC complications in MIS are the following: postoperative epidural hematoma, meningitis, wound infection, parenchymatous brain injury, liquorrhea, hygroma, hemorrhagic conversion of the infarction zone, cosmetic defects [24, 89,98]. All these complications deteriorate MIC course and prognosis, and in some cases can determine the severity of an underlying disease.…”
Section: Malignant Ischemic Stroke Therapymentioning
confidence: 99%
See 1 more Smart Citation